Scientometric study of treatment technologies of soil pollution: present and future challenges - Valdiviezo Gonzales, Lorgio Gilberto (2022)
There are few bibliometric studies showing current technologies and their combinations for the remediation of contaminated soils. For this reason, a scientometric study was carried out in order to know the trends in soil contamination treatment technologies. The study considered original articles and reviews published in the Scopus and Web of Science databases between January 2010 and June 2021, evaluating: (a) characteristics of the publications, (b) main research sources, (c) citations and production by journals, (d) keywords used, (e) countries, institutions and authors active in research production, (f) most cited articles and (g) trends in soil treatment and remediation techniques. The results showed: (a) continuous growth of publications on soil remediation in the “Environmental Science” subject area and a limited contribution of the “Soil Science” and “Agriculture and Biological Science” subject areas, (b) leadership of countries such as China, USA, India, Italy and Spain in research production, (c) phytoremediation, bioremediation and biodegradation were the most studied treatment technologies in the last decade and (d) recent research (from 2020) studied pesticides and herbicides, including Chlorimuron-ethyl and also microplastics and other emerging pollutants. It is also noted that the current trend of combinations of techniques for the treatment of soil contamination is attractive for future research.